Studi Komparasi Metodologi Pembelajaran Islam Model Klasik dan Kontemporer - M. Nurman Ardiansyah; Endin Mujahidin; Santi Lisnawati (TADRIBUNA: Journal of Islamic Education Management, 2025)
Islamic education in its early days was an education with classical methodology, based primarily on the Qur'an, Hadith, and the works of early scholars (yellow books). Meanwhile, the methodology of contemporary Islamic education is more towards combining religious knowledge and general knowledge (science, technology, social). The purpose of this study is to analyze the comparative study of Islamic teaching methodology of the classical and contemporary models. The method used in this study is a qualitative research method, the type of research is library research using descriptive analysis and interpretation analysis, with data collection tools in the form of documents, interviews, and observations. This study confirms that the classical and contemporary Islamic learning models have their respective advantages. The classical model excels in deepening religious knowledge, strengthening morals, and maintaining the sanad of knowledge, while the contemporary model excels in pedagogical innovation, integration of science and technology, and development of 21st-century competencies. However, both also have disadvantages: the classical is less adaptive to the challenges of the times, and the contemporary is prone to losing spiritual depth. Therefore, an integrative approach that combines the strengths of both is very important.